Reset and switch protocols at Landauer limit in a graphene buckled ribbon. (22nd July 2015) - Neri, I.; Lopez-Suarez, M.; Chiuchiú, D.; Gammaitoni, L.
Abstract: Heat produced during a reset operation is meant to show a fundamental bound known as Landauer limit, while simple switch operations have an expected minimum amount of produced heat equal to zero. However, in both cases, present-day technology realizations dissipate far beyond these theoretical limits. In this paper we present a study based on molecular dynamics simulations, where reset and switch protocols are applied on a graphene buckled ribbon, employed here as a nano electromechanical switch working at the thermodynamic limit.